Food consumption behavior of the Malays in Malaysia - Tey, Yeong Sheng; Shamsudin, Mad Nasir; Mohamed, Zainal Abidin; Abdullah, Amin Mahir; Radam, Alias (International Islamic University, Malaysia, 2008)
The objective of this study is to provide an insight into demand patterns of Malay consumers for specific food categories in Malaysia. By utilizing Household Expenditure Survey 2004/2005, a system of equations of Linear Approximate Almost Ideal Demand System (LA/AIDS) model for 12 aggregated food products is estimated using a two-step estimation procedure. A Working-lesser form of Engel function is also estimated to derive income elasticities from the estimated expenditure elasticities. This study shows that Malay consumers appear to have different food consumption patterns as compared to the general Malaysian diets. Malay consumers tend to increase their consumption of rice more than higher-value (meat and fish) and functional (vegetables and fruits) foods. Malay consumers are found to be very sensitive to the own-price of most of the food products, especially rice.